2019
DOI: 10.1136/bmjgh-2018-001087
|View full text |Cite
|
Sign up to set email alerts
|

The impact of user charges on health outcomes in low-income and middle-income countries: a systematic review

Abstract: BackgroundUser charges are widely used health financing mechanisms in many health systems in low-income and middle-income countries (LMICs) due to insufficient public health spending on health. This study systematically reviews the evidence on the relationship between user charges and health outcomes in LMICs, and explores underlying mechanisms of this relationship.MethodsPublished studies were identified via electronic medical, public health, health services and economics databases from 1990 to September 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 43 publications
3
48
0
2
Order By: Relevance
“…Free healthcare policies aim at partially remove financial barriers to accessing healthcare services, with the ultimate goal of reducing the overall burden of morbidity and mortality, including decreasing maternal and child mortality burden [1,2]. Since the year 2000, several interventions of total or partial abolition of direct payment for health care have emerged in many African countries including Burkina Faso [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Free healthcare policies aim at partially remove financial barriers to accessing healthcare services, with the ultimate goal of reducing the overall burden of morbidity and mortality, including decreasing maternal and child mortality burden [1,2]. Since the year 2000, several interventions of total or partial abolition of direct payment for health care have emerged in many African countries including Burkina Faso [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several advantages related to the implementation of partial or total free health care have been described in the literature [1,2,[5][6][7][8][9]. It allows for financial protection of populations [7] and a reduction in household health expenditure [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Cost recovery in public sector was a key component of World Bank's advice for LMICs [106,108]. Studies in India and globally have reported the adverse effects of user fees on access and expenditure of the poor for healthcare [11,42,112,[116][117][118]. User fees could have contributed to the reduction in access to public sector in India.…”
Section: Discussionmentioning
confidence: 99%
“…Some strategies have been developed to address these concerns such as the "zero-mark-up" policy for essential drugs to control cost escalation, and billions of government investment in public health services especially in rural areas to improve efficiency of resource allocation [61]. Further extended health reforms that are embodied in Healthy China 2030, a government blueprint, are needed to meet the ongoing health problems such as chronic diseases, an aging population, and rising expectations of health [55,62,63]. The capacity of primary healthcare system needs further strengthened to manage the rising burden of chronic diseases and health expenditures [62].…”
Section: Policy Implicationsmentioning
confidence: 99%